Density functional theory study of structural, electronic, and thermal properties of Pt, Pd, Rh, Ir, Os and PtPd X (X = Ir, Os, and Rh) alloys. (20th January 2016) - Ahmed, Shabbir; Zafar, Muhammad; Shakil, M; Choudhary, M A
Abstract: The structural, electronic, mechanical, and thermal properties of Pt, Pd, Rh, Ir, Os metals and their alloys PtPd X ( X = Ir, Os and Rh) are studied systematically using ab initio density functional theory. The groundstate properties such as lattice constant and bulk modulus are calculated to find the equilibrium atomic position for stable alloys. The electronic band structure and density of states are calculated to study the electronic behavior of metals on making their alloys. The electronic properties substantiate the metallic behavior for all studied materials. The firstprinciples density functional perturbation theory as implemented in quasi-harmonic approximation is used for the calculations of thermal properties. We have calculated the thermal properties such as the Debye temperature, vibrational energy, entropy and constant-volume specific heat. The calculated properties are compared with the previously reported experimental and theoretical data for metals and are found to be in good agreement. Calculated results for alloys could not be compared because there is no data available in the literature with such alloy composition.